Medical Emergencies Caused by Aquatic Animals: A Biological and Clinical Guide to Trauma and Envenomation Cases, Second Edition - Junior, Vidal Haddad [UNESP] (Springer Nature, 2021)
This is the second edition of the book originally published under the title Medical Emergencies Caused by Aquatic Animals: A Zoological and Clinical Guide. Including updated chapters, new content and additional references, it discusses follow-up with patients, describes diseases that are not emergencies and explains procedures that can take place at health stations and outpatient centers, focusing on clinical and biological aspects relevant to researchers and practitioners alike. The chapter on Invertebrate Aquatic Animals presents facts and advances that were left out of the first edition. In addition, it includes improved images. The subtopic on Cnidaria presents recent data on outbreaks and new species identification in unprecedented areas, with a timely discussion on first aid treatment. The chapter on Injuries by Vertebrate Aquatic Animals has been improved, based on continued work with bathers and fishermen. Featuring numerous images and representative clinical cases, it explores the most significant injuries caused by fish around the globe. The chapter on Ingestion of Aquatic Venomous Animals: Toxinology, Clinical Aspects, and Treatment discusses outbreaks of intoxication diseases from eating fish and seafood, drawing on reliable records of serial cases of Haff's syndrome, scombroidism and ciguatera. Further, it examines the indiscriminate consumption of aquatic animals, which the author argues present the same (or even greater) risks of poisoning and infections as terrestrial animals. Lastly, since there is a general lack of awareness of the risk of infections in aquatic environments, the chapter on Bacterial and Fungal Infections in Aquatic Environments describes the symptoms and treatments and highlights preventive measures.
Keywords: Aquatic animals; Aquatic environments; Bites and stings; Emergencies; Envenomation; Human infections; Poisoning; Toxinology; Trauma; Venomous animals